CRISPR Interference (CRISPRi) Inhibition of luxS Gene Expression in E. coli: An Approach to Inhibit Biofilm - Zuberi, Azna; Misba, Lama; Khan, Asad U. (Frontiers in Cellular and Infection Microbiology, 2017)
Biofilm is a sessile bacterial accretion embedded in self-producing matrix. It is the root cause of about 80% microbial infections in human. Among them, E. coli biofilms are most prevalent in medical devices associated nosocomial infections. The objective of this study was to inhibit biofilm formation by targeting gene involved in quorum sensing, one of the main mechanisms of biofilm formation. Hence we have introduced the CRISPRi, first time to target luxS gene. luxS is a synthase, involved in the synthesis of Autoinducer-2(AI-2), which in turn guides the initial stage of biofilm formation. To implement CRISPRi system for luxS gene suppression, we have synthesized complementary sgRNA to target gene sequence and co-expressed with dCas9, a mutated form of an endonuclease. Suppression of luxS expression was confirmed through qRT-PCR. The effect of luxS gene on biofilm inhibition was studied through crystal violet assay, XTT reduction assay and scanning electron microscopy. We conclude that CRISPRi system could be a potential strategy to inhibit bacterial biofilm through mechanism base approach.